Characterization of Cellulase Enzyme Produced by Two Selected Strains of Streptomyces Macrosporeus Isolated from Soil in Indonesia - Soeka, Yati; Suharna, Nandang; Triana, Evi; Yulinery, Titin (Makara Journal of Science, 2019)
This study was conducted to characterize the cellulase enzymes produced by Streptomyces macrosporeus BB 32 and S.microspores KRC 21. D, which were isolated from Tanjung Pendam, Belitung Island, and from Cibodas Botanical Gar-den, Indonesia, respectively. The optimal activity of the enzymes was analyzed using parameters such as incubationtime, pH, temperature, carboxymethylcellulose (CMC) concentration. The effect of the addition of some metal ions asactivators or inhibitors was also analyzed spectrophotometrically at λ 540 nm. Results demonstrated that the activity of the cellulase enzymes of S. macrosporeus BB 32 and S. macrosporeus KRC 21 D reached the optimum level after 2 and5 days of incubation and at pH values of 8.0 and 6.0, temperatures of 35 °C and 50 °C, and CMC concentrations of 1.75% and 2%, respectively. S. macrosporeus BB 32 cellulase was activated by the cations CuCl2, MgCl2, and ZnCl2but inhibited by NaCl and CoCl2, reducing its activity. The cellulase of S. macrosporeusKRC 21.D was activated bythe cation NaCl and by the divalent cations CoCl2, CuCl2, MgCl2, and ZnCl2.S. macrosporeus BB 32 was deposited at the Indonesian Culture Collection with the collection number InaCC A144.